Simulation of tectonic stress field and prediction of tectonic fracture distribution in Longmaxi Formation in Lintanchang area of eastern Sichuan Basin - Zhang, Douzhong; Tang, Jiguang; Chen, Kongquan; Wang, Kaiming; Zhang, Peixian; He, Guisong; Tuo, Xiusong (Frontiers in Earth Science, 2022)
Shale is a low-porosity and low-permeability reservoir, and structural fractures are the main controlling factor for the migration and accumulation of shale gas. Moreover, tectonic fractures are controlled by the paleo-tectonic stress field. In this paper, the finite element numerical simulation technology is used to analyze the distribution law of the paleo-tectonic stress field, and further, the fracture development area under the superposition of two periods of tectonic stress is predicted using seismic, rock mechanics, and field data. The results show that the tectonic fractures developed in the Lintanchang area are mainly EW- and NNW-trending conjugate shear fractures formed in the Middle Yanshanian period, followed by the NWW- and SWW-trending conjugate shear fractures formed in the late Yanshanian period. The distribution of tectonic fractures is affected by faults, folds, rock physical parameters and tectonic stresses. It is found that the comprehensive fracture coefficients of the anticline core and fault areas are both greater than 1.1, which are the areas with the most developed structural fractures, and these areas have poor shale gas preservation effect. However, the comprehensive fracture coefficients of the western flank of the anticline and the eastern and western dipping ends are between 1.0 and 1.1, which are areas with better shale gas preservation effect. In addition, the development degree of tectonic fractures in the east and northwest areas of the Lintanchang anticline is lower than that in other areas. The comprehensive fracture coefficients of shale in these areas are between 0.9 and 1.0. The shale is in a state of "breaking without cracking", and shale gas can be well preserved.